Effectiveness of the Giant Set Training Method on Body Fat Reduction - Ahmat Khoiru Wahyudin; Antonius Tri Wibowo (Journal Of Sport Education (JOPE), 2025)
This study aims to determine the effectiveness of the giant set training method in the fat loss program on Argo Gym Fitness members. The results of the study can provide an empirical picture of the effect of this method on weight loss and body fat levels. In addition, this study also aims to provide scientific contributions in the field of fitness science, especially in developing effective and efficient training strategies for the community. This type of research uses a quantitative experimental method with a one-group pre-test post-test design. The population of this study was Argo Gym members with a total of ± 60 people. The sampling technique was Purposive Sampling. The sample in this study were members aged 18-27 years at Argo Gym, totaling 10 people. The research instrument used a body composition measuring tool (Karada Scan), observation sheets and exercise records. Data collection techniques used pre-test and post-test. Data analysis techniques in this study used descriptive analysis and inferential analysis (paired sample t- test). The giant set method has been proven effective in reducing body fat percentage. This is evidenced by a decrease in average body fat from 29.87% in the pretest to 28.94% in the posttest. This change was also statistically significant with a p-value of 0.017 (p < 0.05). This study concluded that giant set training positively contributed to improved body composition and recommended its integration into exercise programs aimed at reducing fat and improving fitness.